A agroecologia como alternativa frente à modernização da agricultura: um estudo de caso no município de Coronel Vivida PR - Stasiak, Ana Paula (2013)
The agro-ecological farming has got started by social movements in favor to the rural sustainable development based on environmental, social and economic. Agroecologyis presented as an alternative to modernization of agriculture that repair environmental damage and social damage caused by the green revolution technology disseminated and adopted by the Brazilian government as a development policy based on the economic growth. This paper aims to analyze the agro-ecology alternatively forward the modernization process of the agriculture and the different territorialities provided by the two forms of production, as well as identify the limits and difficulties of territorial agro-ecological practices in Coronel Vivida, held bibliographic review the topic addressed and fieldwork, using a questionnaire addressed to eleven farmers who have comprised three distinct groups related to agro-ecology in the town: Farmers Convention with SAFs; 2) Agro-ecological Farmers; 3) Farmers Convention-Former Agro-ecological Farmers. And interviews with representatives of institutions related to agriculture and agroecology family whose work is in the town. The study of these three groups with different production and commercial organizations had allowed us to observe the process of territorialization and deterritorialization of simultaneous agro-ecological practices, the latter prevails. Another methodology used to characterize the properties sustainable, based on agro-ecological principles, as well as differentiate the analysis was made landscapes through sketches and photographs of the properties studied. This paper outlines the main difficulties faced by the town farmers relationed to agro-ecological production, as well as the main factors which have influenced the abandonment of agro-ecological practices by the Coronel Vivida agro-ecological farmers.